The Application of the K-Nearest Neighbors Method as A Recommendation for The Selection of Departments in Higher Education Based on The Results of Multiple Intelligence Tests - Nuswantari, N; Rachman, Y F; Setiawan, P W D; Prakoso, W D (Journal of physics. Conference series, 2020)
The problem faced by students after graduating from High School or Vocational High School is the difficulty in deciding whether to work immediately or going to college. The next problem for students who will enter college is to choose which major study based on their type of intelligence. Determination of Departments that are inappropriate often makes students unable to do well in lectures. The problem of this study is whether the selection of Departments for the University of PGRI Madiun in 2019 is in accordance with the type of intelligence or not. The purpose of this study is to recommend the selection of Departments at the University of PGRI Madiun students based on Multiple Intelligence test results. This research is quantitative research and data collection is done qualitatively. The research subjects were students of PGRI Madiun University in 2019. The sampling technique used purposive sampling with a sample of 297 students from 4 Faculties and 22 Departments. The technique of collecting data using the multiple intelligence test questionnaire. The research data were analyzed using the K-Nearest Neighbors method. The results of the study showed that the suitability of the choice of Departments of the University of PGRI Madiun students based on multiple Intelligence test for the Faculty of Health and Science had the highest accuracy of 86.36%, Faculty of Teacher Training and Education (Sains) 63.04%, Faculty of Teacher Training and Education (Social) 32.28%, Faculty of Teacher Training and Education (Language) 58.62%, Faculty of Technology 56.67%, Faculty of Economics and Business 48.84%.